ANALYTICAL METHODS IN INFORMATION TECHNOLOGY: A LITERATURE REVIEW ON THE ROLE OF CALCULUS IN IT INNOVATIONS AND SOLUTIONS - Anita Juniarti (Journal of Scientech Research and Development, 2024)
This literature review comprehensively explores the integral role of calculus-based analytical methods in the domain of information technology (IT), demonstrating their crucial contribution to driving innovations and developing cutting-edge solutions. Through a detailed examination of 20 seminal papers, the study highlights how calculus serves as a fundamental framework for optimizing algorithms, enhancing data analysis, and creating more efficient technological systems. The analysis reveals that calculus not only improves computational efficiencies but also fosters theoretical advancements, enabling the exploration of new IT solutions. The review underscores the significance of calculus in various IT applications, from machine learning and cybersecurity to network optimization and big data analytics, demonstrating its pervasive impact across the IT spectrum. Conclusively, this study validates the hypothesis that calculus-based methods are indispensable for the advancement of IT innovations and suggests continuous exploration at the mathematics-technology nexus for future technological progressions.